Restituição e complementação do ICMS na substituição tributária progressiva - Martins, Fábio Andrade (2022)
The chosen theme and object of this theoretical dissertation work has material limited to the field of Law, specifically the field of Tax Law. It is related to the Taxes area, namely with the Tax on Transactions Related to the Circulation of Goods and on Interstate, Intermunicipal and Communication Transport Services – ICMS. The studies focus on a kind of tax refund, that is, the reimbursement of ICMS withheld by tax substitution, when the quantitative dimension of the legal fact performed is lower than the base calculated for the purposes of anticipating tax collection, as well as the possibility that the tax authorities can demand a supplement to the withholding tax when the effective calculation basis proves to be higher than that used by the substitute for withholding the tax. The choice of the topic is justified by the expressiveness that this form of collection contributes to the treasury, as well as the expansion of tax substitution in the Federated States, started back in 2008. In view of the decisions handed down by the Federal Supreme Court in the Extraordinary Appeal 593.849/MG and in the Direct Action of Unconstitutionality n. 2.777/SP, the legal validity of these institutes is questioned, as well as other issues concerning the subject, such as: the fundamentals and legal concepts of progressive tax substitution; the temporal aspect, ownership and the material and procedural conditions for the effective exercise of this right; the possibility of alternate liability of the substituted in the event that the substitute remains in default and/or infringing; and the issue of monetary restatement of amounts to be refunded. The result of methodological bibliographical and secondary research, based on a set of written productions, this dissertation aims to solve the questions posed by analyzing the existing rules in the current Brazilian tax system, from whose conclusions it can be seen the constitutionality of the restitution and complementation of the ICMS-ST, whose validity basis is the need, convenience, practicability and prevalence of the public interest over the private. It is the progressive tax replacement of an anticipation of the payment due by the substituted, so that its refund must be operationalized quickly and always to the substituted, the only competent person to prove the right and demand the return, duly updated. The supplementary liability of the taxpayer is conditioned to the non-existence of the economic translation of the tax to the substituted, nor the collusion of the latter in any fraud perpetrated